2021
DOI: 10.31557/apjcp.2021.22.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-Education on Knowledge of Oral Hygiene and Psychological Distress to the Parents with Leukemia Children

Abstract: Objective:To analyze the effect of psycho-educational intervention on knowledge of oral hygiene and psychological distress to the parents of children suffering from leukemia. Methods: Design of this study was a quasi-experimental pre-posttest control group design. The sample were 70 mothers who had children with leukemia (intervention group = 35 mothers; control group = 35 mothers). The independent variable was psycho-educational, while the dependent variables were oral hygiene knowledge and psychological dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Therefore, improving the knowledge should also improve the attitude and practice toward leukemia. Educational interventions in the public might increase knowledge about the disease and decrease psychological distress in patients and their family members [ 6 ]. In this study, most participants expressed the need to learn more about leukemia to seek prompt medical attention when symptoms appear or to be able to understand doctor's decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, improving the knowledge should also improve the attitude and practice toward leukemia. Educational interventions in the public might increase knowledge about the disease and decrease psychological distress in patients and their family members [ 6 ]. In this study, most participants expressed the need to learn more about leukemia to seek prompt medical attention when symptoms appear or to be able to understand doctor's decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hematopoietic cell transplantation (HCT), despite having the potential to re-establish normal hematopoietic and immune function, is mostly discussed through the risk of significant toxicities [ 5 ]. In this light, most patients and even healthcare providers still believe that the survival rates of patients with leukemia have not remarkably improved over the past few decades, which negatively impacts the decision-making ability and increases psychological distress for patients and their families [ 6 ]. Nation-wide educational programs and targeted educational interventions are needed to increase awareness about recent developments and effective therapy options among leukemia patients and their family members.…”
Section: Introductionmentioning
confidence: 99%
“…20 Psychoeducation can be individual, family, group, or community-based, depending on the target audience. 21 According to the study of Ilya et al 22 , interventions in the form of psychoeducation boost respondents' awareness of dental and oral hygiene and lower their levels of stress. This is consistent with the study's findings, which indicated a major increase or significant increase after respondents received psychoeducation, respectively, with p = 0.001 (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…This intervention also helps establish a trust-based relationship between medical staff and patients, increases the hopes of patients for a cure, builds their confidence in fighting the disease, eliminates their fear and worries about the disease, and relieves their psychological burden. During the mental intervention, these patients were continuously praised and motivated for them to perceive the effects of their subjective efforts, transform their passive behaviors into positive ones, and improve their self-approval, self-adjustment, and self-control abilities, thereby alleviating their annoyance from their external and internal environments ( 19 ). Moreover, the emotional changes of patients were tracked continuously to help them adjust their psychological health state in time.…”
Section: Discussionmentioning
confidence: 99%